The Conflict of Justice and Legal Certainty in the National Criminal Code: A Middle Way - Sari, Agustina Indah Intan; Frans, Mardian Putra (Jurnal Ius Constituendum, 2024)
The research discusses the unclear meaning of Article 53 paragraph (2) of Law No. 1 of 2023 which states that "If in upholding law and justice as referred to in paragraph (1) there is a conflict between legal certainty and justice, judges must prioritize justice." Justice is used for judges to adjudicate cases and certain conditions are used as a benchmark for judges in making decisions. However, there are several existing definitions of justice, there are still many views. The norm in the article has a vagueness of meaning, making it difficult for judges to equate commensurate thoughts. The implication of vagueness results in disparity in the use of justice to be used by judges, this potential disparity needs to be prevented by mediating the conflict between justice and certainty and providing guidance for judges in using justice in their decisions. This research uses a normative research approach. The results showed that judges have the authority to choose justice that contains legal certainty because a just decision is a manifestation of legal certainty, justice itself is born with the freedom of judges. The formulation of Article 53 paragraph (2) of the Criminal Code needs to be interpreted correctly so that there is no disparity in decisions because justice is what the judge wants based on the law to create justice itself.